Tooth loss and cognitive decline in community dwelling older Irish adults: A cross-sectional cohort study. (April 2022) - Winning, Lewis; Naseer, Amara; De Looze, Céline; Knight, Silvin P.; Kenny, Rose Anne; O'Connell, Brian
Abstract: Objectives: To investigate whether tooth loss and related loss of occluding tooth pairs, were associated with cognitive decline in a group of community dwelling older men and women from Ireland. Methods: A group of 2508 men and women, aged 50–93 years, underwent a dental examination as part of The Irish Longitudinal Study of ageing (TILDA). Global cognitive function was assessed using the mini-mental state examination (MMSE). Analysis included multiple logistic regression with adjustment for various confounders. Results: The mean age of participants was 65.5 years (SD 8.1) and 55.3% of the group were female. Three hundred and twenty-nine (13.1%) of the cohort were classified as having a low MMSE with a score ≤ 27. After adjustment for confounding variables, compared to subjects with ≥ 20 teeth, the odds ratio for a low MMSE amongst edentulous was 1.55 (95% CI 1.03–2.34) p  = 0.03, and for those with 1–19 teeth was 1.38 (95% CI 1.03–1.84) p  = 0.04. Having < 10 natural occluding pairs and < 4 posterior occluding pairs also associated with a low MMSE. Conclusions: In this cross-sectional cohort study, tooth loss and related loss of occluding tooth pairs were associated with a low MMSE in a group of older adults from Ireland, independent of various known confounders. Clinical Significance: Dentists should be aware of the potential systemic health implications of patients presenting with tooth loss. Tooth loss may be an important risk indicator for cognitive decline.